Nelly [videorecording (DVD)] - MacKay, Mylene; Guerin, Marie-Claude; Brunet, Catherine (Actor) (Cinema Libre Studio, 2018)
A film inspired by the life and work of Nelly Arcan. A portrait of a fragmented woman, lost between irreconcilable identities: writer, lover, call girl, and star. Several women in one, navigating between great exaltation and great disenchantment. A film mirror of a violent life and a radical work. A tribute to a dense writing, chilling and necessary.